Longitudinal study of N compounds during flood neap and spring tides in the Terengganu River estuary, Malaysia - Suratman, Suhaimi; Abdul Aziz, Azzyati; Mohd Tahir, Norhayati; Hin Lee, Lee (International Journal of Engineering and Technology, 2019)
This study was performed in the Terengganu River estuary, which is connected to the southern part of the South China Sea, to determine the concentrations of surface water nitrogen (N) compounds during a longitudinal survey. In addition, measurements of chlorophyll-a (chl-a) and the fractionation of total DON were also carried out. In general, higher concentrations of N compounds were recorded in lower salinity regions with many anthropogenic activities. The spring tide showed a significant role in controlling the N compounds as higher concentrations were found under this condition. This was probably due to strong currents which led to the resuspension of bottom sediment, thus releasing N compounds. Most of the N compounds showed addition behaviour along the salinity gradient which was more pronounced during the spring tide. A higher percentage of low molecular weight (LMW) total DON was recorded during the neap tide. The LMW fraction correlated well with chl-a concentrations suggesting that the source of this fraction is through direct release from phytoplankton. This longitudinal study shows the importance of measuring N compounds under different tidal conditions for a better understanding of the distribution of N compounds in the estuarine environment.Â